Atypical Antipsychotics and Lithium Induced Neuroleptic Malignant Syndrome associated with Acute Kidney Injury: A Case Report - Shah, Riya S.; Akhani, Sachin K.; Gupta, Sapna D.; Malhotra, Supriya D. (Nepal Journal of Neuroscience, 2024)
Neuroleptic Malignant Syndrome (NMS) is a rare but serious adverse reaction to antipsychotic medications. This case report presents a 56-year-old male with bipolar disorder on a regimen of Olanzapine, Clozapine and Lithium carbonate, who developed typical NMS. He had muscle rigidity, hyperthermia, rhabdomyolysis which led to acute kidney injury. Prompt withdrawal of psychotropic medications and administration of supportive therapies was done, yet the patient's condition deteriorated, leading to Multiple Organ Dysfunction Syndrome (MODS) and eventually mortality. This case shows the complexity of managing NMS in the context of polypharmacy emphasizing the need for vigilance when prescribing antipsychotic combinations and the challenges faced in treating NMS, especially when there are associated complications.